Centrifugal model tests and numerical modeling on overtopping-induced breach processes of landslide dams - Zhang, Lucheng; Zhong, Qiming; Yang, Meng; Peng, Ming; Liu, Jiaxin; Mei, Shengyao; Yan, Zhikun; Shan, Yibo (Frontiers in Earth Science, 2023)
This study used the 400 g-ton geotechnical centrifuge model test system at the Nanjing Hydraulic Research Institute (NHRI) to investigate the breach evolution characteristics and hydrograph process of overtopping-induced breaching of landslide dams. It was achieved by taking advantage of the “time-space amplification” effect created by high-speed rotation using a centrifuge overweight force field. The effects of dam height, slope ratio, and soil gradation on the overtopping failure process of landslide dams were investigated by centrifugal model tests for the first time. In addition, a detailed physically-based dam breach model was developed to simulate the overtopping failure of landslide dams. Results show that the breach process of a landslide dam can be divided into four stages based on the measured breach morphology evolution process and the abrupt variations of breach flow discharge: initial scour on the downstream slope, retrogressive erosion to the dammed lake, erosion along the breach channel, and breach stabilization. Moreover, the peak breach flow is most sensitive to the dam height, followed by the average particle size; the time to peak is mainly affected by the slope ratio, and the relative residual dam height is primarily susceptible to the average particle size. In practice, the calculated results are consistent with the measured results. This study provides a scientific reference for the cognition of the overtopping-induced breach mechanism of landslide dams.